Statistical Designs and Response Surface Techniques for the Optimization of Extra Cellular Peroxidase (Lignin Degrading Enzyme) Production by Using Pleurotus sp. - R. Saranya 2, Sankaranarayana Arathi3 and V. Kaviyarasan1, K. Saravanakumar1* (Recent Research in Science and Technology, 2010)
A response surface methodology (RSM) was used for the optimization of extra cellular laccase production using Pleurotus sp. Central composite experimental design was applied in the analysis of results and this procedure required limited number of experiments performed while providing possible interactions of selected components. Optimum values of tested variables for the maximum laccase production were; mannitol 4.8gm/l, beef extract 3gm/l and pH 6.2 and copper sulphate 4 mg/l, the maximum laccase production was 90.861U/ml. Only 27 experiments were attained this optimum conditions for enzyme production and the coefficient of determination was 89.0%. In the present study, we have demonstrated that the use of central composite factorial design for high yield of enzymes. 1Centre for Advanced studies in Botany, Mycology lab, University of Madras, Chennai, Tamil Nadu, India, 2Department of Biotechnology, JJ College of Arts and Science, Pudukkottai, Trichy, India 3School of chemical and Biotechnology, Sastra University, Thanjavur, Tamil Nadu, India Â 